2018
DOI: 10.1038/nm.4479
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of macrophage cholesterol efflux and atherogenesis by a long noncoding RNA

Abstract: Nuclear receptors regulate gene expression in response to environmental cues, but the molecular events governing the cell-type specificity of nuclear receptors remain poorly understood. Here we outline a role for a non-coding RNA in modulating the cell type-specific actions of LXRs, sterol-activated nuclear receptors that regulate the expression of genes involved in cholesterol homeostasis and that have been causally linked to the pathogenesis of atherosclerosis. We identify the lncRNA MeXis as an amplifier of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 50 publications
2
153
0
1
Order By: Relevance
“…(B) ChIP-Seq bedgraph of LXRα and LXRβ binding patterns in mouse macrophages at the promoter region of the Gramd1b locus (Sallam et al, 2018; Sallam et al, 2016; Zhang et al, 2017). Input (Ctrl) served as a control for LXR enrichment.…”
Section: Figurementioning
confidence: 99%
“…(B) ChIP-Seq bedgraph of LXRα and LXRβ binding patterns in mouse macrophages at the promoter region of the Gramd1b locus (Sallam et al, 2018; Sallam et al, 2016; Zhang et al, 2017). Input (Ctrl) served as a control for LXR enrichment.…”
Section: Figurementioning
confidence: 99%
“…Macrophage cholesterol efflux is mediated mainly by the cholesterol transporters ATP-binding cassette transporter (ABC)-A1 and ABCG1 (4). The expression of these transporters is tightly regulated by transcription factors (TFs), such as liver X receptors (LXRs) and peroxisome proliferator activated receptor g (PPARg) (5)(6)(7)(8); by coregulators, such as nuclear receptor corepressor 1 (NCOR1) and nuclear receptor coactivator 5 (NCOA5) (9,10); and by long, noncoding RNAs, such as macrophage-expressed LXR-induced sequence (MeXis), that specifically regulate LXR-dependent Abca1 expression (11). Macrophage ABCA1 is also involved in inflammatory regulation, as macrophage-specific Abca1 or Abcg1 knockout (KO) mice display decreased cholesterol efflux and enhanced proinflammatory gene expression (12)(13)(14).…”
mentioning
confidence: 99%
“…Lack of MeXis in mouse BMDMs affected the structure of the Abca1 loci, had a negative impact on cholesterol overload and promoted plaque formation. Mechanically, the transcriptional coactivator DDX17 was recruited to the promoter of MeXis and magnified the LXR‐dependent transcription of Abca1 . Work by Chen et al showed that lncRNA GAS5 was highly expressed not only in the plaque of atherosclerosis patients but also in animal models.…”
Section: Inflammatory Diseases Induced By Dysregulation Of Lncrnas Anmentioning
confidence: 99%